Rząd czy nierząd? Socjologiczna refleksja nad kondycją moralną społeczeństwa polskiego - Budzyńska, Ewa (Acta Universitatis Lodziensis. Folia Sociologica, 2012)
The axionormative order is endowed with its own structure and dynamics. It is comprised of the institutional-ideological system (the ethics), the socially recognised axionormative system, and morality manifesting itself in social consciousness and human actions. The three aforementioned spheres are related to one another by means of ties assuming a form of order or, contrariwise, disorder (the anomie). In the context of Polish society, one may discern all types of axionormative order (such as, for instance, conformity with reference to the ethics of Catholicism or to one of the two other axionormative systems manifested in social consciousness), many types of disorder (they most often assume the Mertonian forms of innovation, retreatism and rebellion), as well as Znaniecki’s a cultural conflict.